Use of complementary and integrative health in Finland: a cross-sectional survey - Maija Pyykkönen; Pauliina Aarva; Salla Ahola; Matti Pasanen; Kaija Helin (BMC Complementary Medicine and Therapies, 2023)
Abstract Background Population based studies have shown large differences in the estimated prevalence of complementary and integrative health (CIH) usage between studies. This is in part due to there being no golden standard definition for CIH. In Finland, an updated and internationally comparable study on the prevalence of CIH usage is needed. In the present study, a modified Finnish version of the International Questionnaire to Measure Use of Complementary and Alternative Medicine (I-CAM-QFI) was utilised to examine prevalence of use of different CIH modalities and their experienced helpfulness in the general Finnish population. Methods Respondents aged 16 and above were invited to take part in this descriptive cross-sectional study through an online panel in December 2022. The usage of CIH and the experienced helpfulness were calculated with SPSS (v28) as the proportion of users per each modality. The data were weighted based on gender, age and place of residence. Results A total of 3244 respondents completed the survey. CIH was used by 51.1% (95%CI: 49.4–52.8) of the respondents in the 12 months prior to the survey. Self-help practices were the most used category of CIH (28.8%; 95%CI: 27.3–30.4). The prevalence of usage of CIH natural remedies excluding vitamins and minerals was 27.0% (95%CI: 25.5–28.6). CIH providers were visited by 20.4% of the respondents (95%CI: 19.0–21.8). Getting help for a long-term illness or improvement of well-being were often mentioned as the most important reason for the use of different CIH modalities. CIH was generally used more by women compared to men. The large majority found the modalities they used helpful. Conclusions The results increase current understanding on CIH usage in Finland. As the majority of users experience CIH as helpful, there is a need to study CIH in the context of public health policies. The estimates of CIH usage are highly dependent on what is considered as CIH, and this should be paid attention to in future studies.